Pengaruh Good Corporate Governance , Ukuran Perusahaan dan Leverage terhadap kinerja Keuangan Perusahaan - Nurcahya, Adi Sindhu; Wahyuni, Endang Dwi; Setyawan, Setu (Jurnal Reviu Akuntansi dan Keuangan)
This research aims to empirically prove that influence the size of commissioners, size of independent commissioners, size of directors, the size of audit committee, the size of corporation andleverage toward corporation’s financial performances partially and simultaneously. The objectof this research is manufacturing corporation sector and chemical industry base which is registered in indonesian stock exchange 2012-2013.The date which is used is secondary data directlyobatained from website of BEI and each of corporations’ website by using documentationtehcnique. The data is analyzed by using double regression analysis method and hypotheses.This research concludes that simultaneously test shows the result that commssioners variable,independent commssioners, directors, audit committee, size of corporation,and Leverage whichhas positive influence and significant on the change of financial performance dependent variable. Meanwhile partially test shows the result that only variable of directors and leveragewhich has significantly influence toward financial performance and partially commissionersvariable, indeopendent coommissioners,audit committee,and the size of corporation do not havethe significant influence toward financial performances.Ke ywords: Size of commissioners, size of independent commissioners, size of directors, size ofaudit committee, size of the corporation,and Leverage, financial performance.